Advancement, Simplification and Piloting of Electrical Proso Millet De-Husker (Chino Kutak) - Bhandari, Ganga Ram; Gauchan, Devendra; Bhandari, Bharat; Joshi, Bal Krishna; Panta, Saroj (Journal of Nepal Agricultural Research Council, 2021)
Proso millet is a minor cereal crop commonly cultivated in rain fed marginal uplands particularly in the mid and far western mountain region of Nepal. It is potential crop for ensuring food and nutrition security and conservation of local crop biodiversity in high mountain region. Traditionally Proso millet (locally as chino) is processed manually on Mortar and Pestle (Okhal) by using muscular power. However, de-husking (pearling) of Proso millet is very tedious job. The traditional method of processing takes 1 hour to dehusk 2 kg – 3 kg of Proso millet for two women and cause lots of physical exertion to them. Therefore, GEF UNEP Local Crop Project in collaboration with Agricultural Engineering Divisionof NARC initiated program in 2017to design, fabricate and test electric Proso Millet de-husking machine (called chino kutak) that is safe and economical in operation for the use of the local farmers of remote Himalayan region. The model-1 designed, fabricated and piloted at Humla (Chhipra, Kharpunath Rural Municipality) in 2018 was improvised version of Finger millet processing machine. The Model-2 was based on the Centrifugal type working on impact principle was developed in January 2020. The Model-2 was very much successful in all variety of Proso millet and higher capacity up to 52.5 kg/hr.it is equally applicable to other millets.